2021
DOI: 10.3389/fonc.2021.757993
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in the First-Line Treatment of NSCLC: Current Status and Future Directions in China

Abstract: Lung cancer causes significant morbidity and mortality in China and worldwide. In China, lung cancer accounts for nearly one-fourth of all cancer deaths. Non-small cell lung cancer (NSCLC) is the predominant type of lung cancer, accounting for approximately 80%–85% of all lung cancer cases. Immunotherapy with immune checkpoint inhibitors (ICIs) is revolutionizing the treatment of NSCLC. Immune checkpoint molecules, including PD-1/PD-L1 and CTLA-4, can suppress immune responses by delivering negative signals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 111 publications
(137 reference statements)
0
18
0
Order By: Relevance
“…Immune checkpoint inhibitors, including monoclonal antibodies against programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), either as monotherapy or combination therapy, have made a breakthrough in clinical treatment for patients with advanced NSCLC ( 86 ). However, subgroup analyses from several clinical trials demonstrated that no PFS and/or OS benefit was achieved from anti-PD-1/PD-L1 therapy in the patients harboring EGFR mutations ( 87 89 ).…”
Section: Clinical Implications In Advanced Egfr-mutated Nsclc Patient...mentioning
confidence: 99%
“…Immune checkpoint inhibitors, including monoclonal antibodies against programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), either as monotherapy or combination therapy, have made a breakthrough in clinical treatment for patients with advanced NSCLC ( 86 ). However, subgroup analyses from several clinical trials demonstrated that no PFS and/or OS benefit was achieved from anti-PD-1/PD-L1 therapy in the patients harboring EGFR mutations ( 87 89 ).…”
Section: Clinical Implications In Advanced Egfr-mutated Nsclc Patient...mentioning
confidence: 99%
“…The incidence and mortality of cancer have increased rapidly in recent years, of which solid tumors account for the majority ( 1 ). According to the data from the Global Cancer Observatory, lung cancer accounts for 23.8% of all cancer deaths ( 2 ), of which non-small cell lung cancer (NSCLC) accounts for 85% of the diagnoses ( 3 ). Studies on antitumor treatments have greatly developed, but an effective therapy is still important and urgent ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), including programmed death molecule 1 (PD-1) and cytotoxic T cell associated antigen 4 (CTLA-4) inhibitors, have substantially improved the prognosis of a variety of cancers ( 1 3 ). Although ICIs have become the first-line treatment for a variety of solid tumors, immune related adverse events (irAEs) are increasingly recognized with the widespread utilization of these drugs ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, PD-1 or CTLA-4 combined with its ligands can inhibit T cell activation, prevent over activation of human immune system and avoid autoimmune diseases ( 1 3 ). As important advances in tumor therapy in recent years, ICIs mainly take effect by inhibiting immune checkpoints through antibodies [such as PD-1, Programmed cell death 1 ligand 1 (PD-L1), CTLA-4, etc.…”
Section: Introductionmentioning
confidence: 99%